2000
DOI: 10.1161/01.cir.102.12.1420
|View full text |Cite
|
Sign up to set email alerts
|

Functional Protection by Acute Phase Proteins α 1 -Acid Glycoprotein and α 1 -Antitrypsin Against Ischemia/Reperfusion Injury by Preventing Apoptosis and Inflammation

Abstract: Background-Ischemia followed by reperfusion (I/R) causes apoptosis, inflammation, and tissue damage leading to organ malfunction. Ischemic preconditioning can protect against such injury. This study investigates the contribution of the acute phase proteins ␣ 1 -acid glycoprotein (AGP) and ␣ 1 -antitrypsin (AAT) to the protective effect of ischemic preconditioning in the kidney. Methods and Results-Exogenous AGP and AAT inhibited apoptosis and inflammation after 45 minutes of renal I/R in a murine model. AGP an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
132
0
1

Year Published

2001
2001
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 168 publications
(136 citation statements)
references
References 39 publications
3
132
0
1
Order By: Relevance
“…In the motif, R ϭ G or A, W ϭ T or A, Y ϭ C or T. Several human genes whose expression is positively regulated by wild-type p53 have been identified. These include mdm2 (5), bax (6), gadd45 (7), proliferating cell nuclear antigen (8), p21/WAF1 (9), insulin-like growth factor-binding protein 3 (IGFBP3) 1 (10), the muscle creatine kinase gene, thrombospondin-1 (11), vascular smooth muscle ␣-actin gene (ACTA) (12), epidermal growth factor receptor (13), and type IV collagenase (MMP-2) (14). Although the number of identified p53 target genes keeps growing, it is conceivable that large fraction of the p53 target genes have not yet been identified.…”
mentioning
confidence: 99%
“…In the motif, R ϭ G or A, W ϭ T or A, Y ϭ C or T. Several human genes whose expression is positively regulated by wild-type p53 have been identified. These include mdm2 (5), bax (6), gadd45 (7), proliferating cell nuclear antigen (8), p21/WAF1 (9), insulin-like growth factor-binding protein 3 (IGFBP3) 1 (10), the muscle creatine kinase gene, thrombospondin-1 (11), vascular smooth muscle ␣-actin gene (ACTA) (12), epidermal growth factor receptor (13), and type IV collagenase (MMP-2) (14). Although the number of identified p53 target genes keeps growing, it is conceivable that large fraction of the p53 target genes have not yet been identified.…”
mentioning
confidence: 99%
“…Marcondes et al reported that AAT alters the cellular redox state and improves mitochondrial membrane potential while also increasing expression of antioxidant enzymes such as heme oxygenase 1 (Figure 1). 4, 5, 6, 7 Oxidative stress is important in inflammation and IRI, so these activities may contribute to the ability of AAT to promote cell and tissue survival and modulate inflammatory damage 10, 11, 13, 14, 15, 16, 17, 18, 19, 20. Because different types of lymphocytes, and cells in different activation states, differ in dependence on glycolysis vs oxidative phosphorylation, modulation of mitochondrial function may influence the balance between sensitization and tolerance 6…”
Section: Novel Functions Of Aatmentioning
confidence: 99%
“…AAT has been shown to inhibit apoptosis in multiple in vitro and in vivo models 10, 11, 13, 14, 15, 16, 17, 18, 19, 20. Increased cell survival may result not only from stabilization of mitochondrial membranes, but also likely involves direct inhibition of caspases (Figure 1).…”
Section: Novel Functions Of Aatmentioning
confidence: 99%
See 1 more Smart Citation
“…While being one of the most important binding proteins in plasma [17], AGP also features several immunomodulatory functions [16], such as, for example, the stimulation of human monocytes to release pro-and anti-inflammatory cytokines [36], the inhibition of the chemotactic response of human neutrophils challenged with formyl-methionyl-leucyl-phenylalanine (fMLP) [19,41] and the reduction of platelet aggregation [35]. Moreover, AGP is capable of protecting cells from apoptosis induced by inflammation [7][8][9]. In this study it was first hypothesized that AGP may modulate the chemotactic response of bovine defensive cells, including monocytes and polymorphonuclear cells.…”
Section: Introductionmentioning
confidence: 99%